A surface nitrided lithium battery silicon-based negative electrode material and preparation method thereof

The mixed pickling and polysilazane impregnation of hydrochloric acid and high-temperature heat treatment are carried out to form silicon particles of amorphous silicon nitride coating, which solves the problem of volume expansion and interface instability of the silicon negative electrode material and improves the electrochemical performance and stability of lithium batteries.

CN119160895BActive Publication Date: 2025-03-25NANCHANG INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411641688.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-25
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

Silicon, as the negative electrode material for lithium-ion batteries, has problems with volume expansion and interface instability, resulting in limited battery cycle stability and life.

Method used

The mixed pickled silicon powder of hydrochloric acid-hydrofluoric acid is used to remove oxygen and decontamination, impregnate polysilazane, and undergo high-temperature heat treatment to form an amorphous silicon nitride coating layer, and the modified silicon particles are used for the negative electrode material of lithium battery.

Benefits of technology

The first deliquency capacity and first Coulomb efficiency of the silicon negative electrode are improved, the powdering of silicon particles and the repeated formation of SEI film are inhibited, and the cycle stability and life of the battery are extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160895B_ABST
    Figure CN119160895B_ABST
Patent Text Reader

Abstract

The present invention provides a surface nitrided silicon-based negative electrode material for lithium batteries and a preparation method thereof, which belongs to the technical field of negative electrodes for lithium batteries. The preparation method comprises the following steps: immersing silicon powder in an acid solution for pickling to remove oxygen and impurities, repeatedly rinsing with deionized water and then drying; then immersing in liquid polysilazane, filtering after sufficient stirring, obtaining silicon powder with surface impregnated with polysilazane; then preheating the silicon powder and performing high-temperature thermal cracking; the silicon powder after thermal cracking is placed in an organic solvent for soaking and cleaning, then repeatedly rinsed with water, and dried to obtain silicon particles with surface nitridation, which are used as silicon-based negative electrode materials for lithium batteries. The present invention removes oxygen and impurities by mixing acid-washed silicon powder, then immerses in polysilazane, and then obtains amorphous silicon nitride-coated silicon powder by high-temperature heat treatment, and then obtains surface nitrided silicon particles by washing and drying with acetone, and efficiently and uniformly coats a layer of amorphous silicon nitride on the surface of the silicon particles, thereby improving the first lithium removal capacity and the first coulomb efficiency of the silicon negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery negative electrodes, and in particular relates to a surface nitrided lithium battery silicon-based negative electrode material and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have attracted widespread attention among the new generation of energy materials due to their good cycle stability, high energy density, and environmental protection. The traditional negative electrode material for lithium-ion batteries is graphite, but its theoretical specific capacity is only about 372mAh / g. Due to this limitation, traditional graphite negative electrode materials are almost at their limit in improving the range of lithium batteries. In this context, silicon negative electrodes have received widespread attention due to their theoretical specific capacity of up to 4200mAh / g, and are currently the most effective negative electrode materials for solving the problem of long-range electric vehicles.

[0003] Silicon, as a negative electrode material for lithium-ion batteries, currently has two major problems: first, its volume expands by up to 300% during the process of charging and discharging and deintercalating lithium, causing the silicon negative electrode to pulverize and fall off, reducing the battery cycle stability; second, the interface is unstable. During the charging and discharging process of the silicon negative electrode, the solid electrolyte interface layer SEI on the electrode surface is easily broken, causing the exposed silicon to repeatedly react with the electrolyte to form an SEI film, resulting in the consumption of the electrolyte, affecting the performance and life of the battery.

[0004] Surface modification of silicon anode is an effective technical means to alleviate the problems of silicon anode materials, among which surface nitridation modification is widely used. At present, conventional surface nitridation modification methods mainly include: (1) using nitrogen, ammonia, liquid ammonia, etc. as inorganic nitrogen sources, through chemical deposition combined with heat treatment, to promote the diffusion and penetration of active nitrogen atoms into the silicon powder, and then form silicon nitride as a coating layer on the surface of silicon powder. Its disadvantages are uneven composition of the coating layer, difficult to control thickness, complex process and high cost; (2) using urea, glycine, melamine, thiourea, thiocyanate, dopamine, etc. as organic nitrogen sources, through heat treatment, the functional groups of the organic nitrogen source are combined with silicon atoms to form chemical bonds, and then form a coating layer on the surface of silicon powder. The coating layer is generally a polymer of the organic nitrogen source. Its disadvantage is that the heat treatment itself cannot produce silicon nitride, and it needs to rely on the reaction of the nitrogen source and silicon powder to form a coating layer, and then only local coating can be achieved; if the coating effect is to be improved, dispersants, activators or mechanical / ultrasonic dispersion are required to promote the reaction of nitrogen source and silicon powder. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a surface nitrided lithium battery silicon-based negative electrode material and a preparation method thereof, aiming to solve at least one technical problem in the background technology.

[0006] The present invention is achieved in that:

[0007] The first aspect of the present invention provides a method for preparing a surface nitrided lithium battery silicon-based negative electrode material, the preparation method comprising the following steps:

[0008] The silicon powder is immersed in an acid solution for pickling to remove oxygen and impurities, and then repeatedly rinsed with deionized water and dried;

[0009] The acid-washed silicon powder is immersed in liquid polysilazane, fully stirred and then filtered to obtain silicon powder with the surface impregnated with polysilazane;

[0010] The silicon powder after the impregnation treatment is heat-treated, and the heat treatment is preheating and then thermal cracking; the preheating temperature is 240°C to 260°C, and the thermal cracking temperature is 800°C to 1000°C;

[0011] The surface nitrided silicon powder is immersed in an organic solvent for cleaning, and then repeatedly rinsed with deionized water. After drying, surface nitrided silicon particles are obtained, which are used as silicon-based negative electrode materials for lithium batteries.

[0012] Furthermore, the heat treatment is specifically performed as follows:

[0013] The silicon powder after the impregnation treatment is loosely packed in a ceramic crucible, and the ceramic crucible is placed in the uniform temperature zone of a tube furnace; nitrogen-containing gas is input to evacuate the inside of the tube furnace;

[0014] Heat up at a rate of 5℃ / min~10℃ / min, and keep the temperature for 3h±0.5h after the uniform temperature zone reaches the preheating temperature of 240℃~260℃;

[0015] After the insulation is completed, the temperature is increased at a rate of 5℃ / min~10℃ / min, and the uniform temperature zone is raised to the thermal cracking temperature of 800℃~1000℃ and then maintained for 2h±0.5h;

[0016] The product is then cooled to room temperature in the furnace to obtain silicon powder with surface nitrided.

[0017] Furthermore, the nitrogen-containing gas is selected from at least one of nitrogen and ammonia, and its purity is ≥99.999%.

[0018] Furthermore, the acid solution is a mixed acid solution of 1wt.% to 5wt.% hydrofluoric acid and 5wt.% to 10wt.% hydrochloric acid.

[0019] Furthermore, the solid-liquid ratio of the silicon powder to the acid solution is 1:10-1:20.

[0020] Furthermore, the silicon powder is immersed in the acid solution for pickling for 3h±0.5h.

[0021] Furthermore, the organic solvent is acetone.

[0022] The second aspect of the present invention provides a surface nitrided lithium battery silicon-based negative electrode material obtained by the above preparation method.

[0023] Furthermore, the silicon-based negative electrode material of the lithium battery is silicon particles with amorphous silicon nitride coated on the surface.

[0024] The invention removes oxygen and impurities by washing silicon powder with a mixed hydrochloric acid-hydrofluoric acid, then impregnates with polysilazane, and then performs high-temperature heat treatment to obtain amorphous silicon nitride-coated silicon powder, and finally washes and dries with acetone to obtain silicon particles with surface nitridation modification.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The present invention adopts a polysilazane precursor pyrolysis method to efficiently and uniformly coat a layer of amorphous silicon nitride on the surface of silicon particles, thereby improving the first lithium removal capacity and the first coulombic efficiency of the silicon negative electrode.

[0027] (2) The process of the present invention is simple, has low requirements on equipment, has relatively low cost, short production cycle, and is easy to implement large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a SEM image of silicon particles after surface nitridation modification treatment in Example 1 of the present invention.

[0029] Figure 2 This is a TEM image of silicon particles after surface nitridation modification treatment in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific implementation cases described herein are only used to explain the present invention and are not used to limit the present invention.

[0031] A method for preparing a surface nitrided lithium battery silicon-based negative electrode material comprises steps S11 to S14.

[0032] S11, silicon powder pretreatment;

[0033] The silicon powder is immersed in acid solution for acid washing to remove oxygen and impurities, and then repeatedly washed with deionized water for 3 to 7 times, and then the precipitate is dried;

[0034] The acid solution is a mixed acid solution of 1wt.% to 5wt.% hydrofluoric acid and 5wt.% to 10wt.% hydrochloric acid, for example, 3wt.% hydrofluoric acid + 10wt.% hydrochloric acid, 5wt.% hydrofluoric acid + 7wt.% hydrochloric acid, 1wt.% hydrofluoric acid + 5wt.% hydrochloric acid; the following embodiments are illustrated by 3wt.% hydrofluoric acid + 10wt.% hydrochloric acid, but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0035] The solid-liquid ratio of silicon powder to acid solution is 1:10 to 1:20, for example, 1:10, 1:15, 1:20; the following embodiments are illustrated by 1:20, but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0036] The pickling time of silicon powder immersed in acid solution is 3h±0.5h; for example, it can be 2.5h, 3h, 3.5h; the following embodiment is illustrated by 3h, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0037] S12, the surface of silicon powder is treated by impregnation with polysilazane;

[0038] The silicon powder treated in step S11 is placed in liquid polysilazane, fully stirred, and then excess polysilazane is filtered out. The silicon powder after the soaking is stored for later use.

[0039] S13, silicon powder surface nitridation;

[0040] The silicon powder after the impregnation treatment in step S12 is loosely packed in a ceramic crucible, and the ceramic crucible is placed in the uniform temperature zone of the tube furnace; the inside of the tube furnace is evacuated with nitrogen-containing gas; the nitrogen-containing gas is selected from at least one of nitrogen and ammonia, and its purity is ≥99.999%; so that the tube furnace is in a non-oxidizing atmosphere to avoid oxidation reaction of silicon powder and polysilazane during subsequent heat treatment;

[0041] The temperature is raised at a rate of 5°C / min to 10°C / min, and the temperature in the uniform temperature zone is kept at the preheating temperature for 3h±0.5h; after the temperature is kept at the same temperature, the temperature is raised at a rate of 5°C / min to 10°C / min, and the temperature in the uniform temperature zone is raised to the thermal cracking temperature and kept at the same temperature for 2h±0.5h; then the temperature is cooled to room temperature with the furnace to obtain silicon powder with surface nitridation;

[0042] The heating rate is set to 5°C / min~10°C / min, for example, 5°C / min, 10°C / min; but not limited to the listed values, other values ​​not listed within the numerical range are also applicable;

[0043] The preheating temperature is set to 240°C~260°C, for example, it can be 240°C, 250°C, 260°C; the following embodiment is illustrated by 250°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; in the preheating temperature range of 240°C~260°C, polysilazane undergoes a crosslinking reaction, condensation and cleavage of bonds occur between organic functional groups, and the molecular weight increases, which is conducive to promoting subsequent thermal cracking into inorganic silicon nitride; if the preheating temperature is too low, the crosslinking reaction is incomplete, affecting the subsequent thermal cracking; if the preheating temperature is too high, the nitrogen element escapes and volatilizes too much in the form of nitrogen-containing gas, which is not conducive to the subsequent formation of silicon nitride;

[0044] The thermal cracking temperature is set to 800°C~1000°C, for example, it can be 800°C, 900°C, 1000°C; but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable; in the temperature range of 800°C~1000°C, organic matter is converted into inorganic matter, and organic groups decompose to form amorphous silicon nitride; if the thermal cracking temperature is too low, the conversion is incomplete, and if the thermal cracking temperature is too high, amorphous silicon nitride is converted into crystalline silicon nitride, which is not conducive to improving the electrochemical properties of the material.

[0045] S14, soaking and cleaning the silicon powder after the surface nitridation treatment in step S13 in an organic solvent acetone, and then repeatedly rinsing with deionized water, and drying to obtain silicon particles with surface nitridation modification, that is, silicon particles with amorphous silicon nitride coated on the surface.

[0046] The present invention removes oxygen and impurities by washing silicon powder with a mixed hydrochloric acid-hydrofluoric acid, then impregnates polysilazane, and then performs high-temperature heat treatment to obtain amorphous silicon nitride-coated silicon powder, and then washes and dries with acetone to obtain the final surface nitrided silicon powder. The present invention coats a layer of amorphous silicon nitride on the surface of silicon particles to inhibit pulverization of silicon particles, thereby inhibiting the repeated formation of SEI films, and can improve the first coulomb efficiency of the silicon negative electrode.

[0047] The surface nitrided silicon powder prepared by the present invention can be directly used as the negative electrode material of lithium ion batteries, and can also be compounded with carbon materials (such as graphite, carbon nanotubes, etc.) to prepare C / Si negative electrode materials.

[0048] Example 1

[0049] A method for preparing a surface nitrided lithium battery silicon-based negative electrode material, comprising the following steps:

[0050] Step 1, weigh 10g of silicon powder, add 3wt.% hydrofluoric acid and 10wt.% hydrochloric acid at a solid-liquid ratio of 1:20 and stir, stir once every 30min during the reaction, react for 3h, take the precipitate and wash it with deionized water 7 times after the reaction, dry the precipitate at 50°C to obtain pretreated silicon powder;

[0051] Step 2: placing the silicon powder pretreated in step 1 into liquid polysilazane, stirring thoroughly, filtering out excess polysilazane, and storing the impregnated silicon powder for later use;

[0052] Step 3, weigh 5g of the silicon powder obtained in step 2, loosely pack it in a ceramic crucible, and then place the ceramic crucible in the uniform temperature zone of a tubular furnace; exhaust with high-purity nitrogen at a flow rate of 100ml / min for 30 minutes, heat to 250℃ at a rate of 10℃ / min and keep warm for 3h, then heat to 800℃ at a rate of 10℃ / min and keep warm for 2h, then cool to room temperature with the furnace, and take out the silicon powder;

[0053] Step 4: Soak the silicon powder in acetone for 10 minutes, then rinse it with deionized water for 7 times, and dry it to obtain silicon powder for use, which is the silicon particles with surface nitridation modification.

[0054] Figure 1 This is a SEM image of the silicon particles modified by surface nitridation in Example 1. It can be seen that the silicon particles are irregular flakes with a size of submicron level. Figure 2 This is a TEM image of the silicon particles modified by surface nitridation in Example 1. It can be seen that after nitridation modification, the surface of the silicon particles is uniformly coated with a layer of amorphous silicon nitride.

[0055] Example 2

[0056] This embodiment 2 is a method for preparing a surface nitrided lithium battery silicon-based negative electrode material, which differs from embodiment 1 only in the heating rate during preheating in step 3.

[0057] Step three of Example 2 is as follows: weigh 5 g of the silicon powder obtained in Step 2, loosely pack it in a ceramic crucible, and then place the ceramic crucible in the uniform temperature zone of a tubular furnace; exhaust with high-purity nitrogen at a flow rate of 100 ml / min for 30 minutes, heat to 250°C at a rate of 5°C / min and keep warm for 3 hours, then heat to 800°C at a rate of 10°C / min and keep warm for 2 hours, then cool to room temperature with the furnace and take out the silicon powder.

[0058] Example 3

[0059] This embodiment 3 is a method for preparing a surface nitrided lithium battery silicon-based negative electrode material, which differs from embodiment 1 only in the heating rate during pyrolysis in step 3.

[0060] Step three of Example 3 is as follows: weigh 5 g of the silicon powder obtained in step two, loosely pack it in a ceramic crucible, and then place the ceramic crucible in the uniform temperature zone of a tubular furnace; exhaust with high-purity nitrogen at a flow rate of 100 ml / min for 30 minutes, heat to 250°C at a rate of 10°C / min and keep warm for 3 hours, then heat to 800°C at a rate of 5°C / min and keep warm for 2 hours, then cool to room temperature with the furnace and take out the silicon powder.

[0061] Example 4

[0062] This embodiment 4 is a method for preparing a surface nitrided lithium battery silicon-based negative electrode material, which differs from embodiment 1 only in the pyrolysis temperature of step three.

[0063] Step three of Example 4 is as follows: weigh 5 g of the silicon powder obtained in step two, loosely pack it in a ceramic crucible, and then place the ceramic crucible in the uniform temperature zone of a tubular furnace; exhaust with high-purity nitrogen at a flow rate of 100 ml / min for 30 minutes, heat to 250°C at a rate of 10°C / min and keep warm for 3 hours, then heat to 900°C at a rate of 10°C / min and keep warm for 2 hours, then cool to room temperature with the furnace and take out the silicon powder.

[0064] Example 5

[0065] This embodiment 5 is a method for preparing a surface nitrided lithium battery silicon-based negative electrode material, which differs from embodiment 1 only in the pyrolysis temperature of step three.

[0066] Step three of Example 5 is as follows: weigh 5 g of the silicon powder obtained in step two, loosely pack it in a ceramic crucible, and then place the ceramic crucible in the uniform temperature zone of a tubular furnace; exhaust with high-purity nitrogen at a flow rate of 100 ml / min for 30 minutes, heat to 250°C at a rate of 10°C / min and keep warm for 3 hours, then heat to 1000°C at a rate of 10°C / min and keep warm for 2 hours, then cool to room temperature with the furnace and take out the silicon powder.

[0067] Comparative Example 1

[0068] This comparative example 1 is a method for preparing a surface nitrided lithium battery silicon-based negative electrode material, which differs from Example 1 only in the pyrolysis temperature of step three.

[0069] Step three of this comparative example 1 is specifically as follows: weigh 5 g of the silicon powder obtained in step two, loosely pack it in a ceramic crucible, and then place the ceramic crucible in the uniform temperature zone of a tubular furnace; exhaust with high-purity nitrogen at a flow rate of 100 ml / min for 30 minutes, heat to 250°C at a rate of 10°C / min and keep warm for 3 hours, then heat to 1100°C at a rate of 10°C / min and keep warm for 2 hours, then cool to room temperature with the furnace, and take out the silicon powder.

[0070] Comparative Example 2

[0071] Comparative Example 2 is a method for preparing a surface nitrided lithium battery silicon-based negative electrode material, which differs from Example 1 only in the pyrolysis temperature of step three.

[0072] Step three of this comparative example 2 is specifically as follows: weigh 5 g of the silicon powder obtained in step two, loosely pack it in a ceramic crucible, and then place the ceramic crucible in the uniform temperature zone of a tubular furnace; exhaust with high-purity nitrogen at a flow rate of 100 ml / min for 30 minutes, heat to 250°C at a rate of 10°C / min and keep warm for 3 hours, then heat to 700°C at a rate of 10°C / min and keep warm for 2 hours, then cool to room temperature with the furnace and take out the silicon powder.

[0073] Comparative Example 3

[0074] Comparative Example 3 is a method for preparing a surface nitrided lithium battery silicon-based negative electrode material, which differs from Example 1 only in that the preheating step is deleted in step three.

[0075] Step 3 of this comparative example 3 is specifically as follows: weigh 5 g of the silicon powder obtained in step 2, loosely pack it in a ceramic crucible, and then place the ceramic crucible in the uniform temperature zone of a tubular furnace; exhaust with high-purity nitrogen at a flow rate of 100 ml / min for 30 minutes, heat to 800°C at a rate of 10°C / min and keep it for thermal cracking for 2 hours, then cool it to room temperature with the furnace, and take out the silicon powder.

[0076] Comparative Example 4

[0077] Comparative Example 4 is a method for preparing a silicon-based negative electrode material for a lithium battery, which differs from Example 1 only in that the polysilazane impregnation step is deleted.

[0078] The preparation method of this comparative example 4 is specifically as follows:

[0079] Step 1: Weigh 100g of silicon powder, add 3wt.% hydrofluoric acid and 10wt.% hydrochloric acid at a solid-liquid ratio of 1:20 and stir. Stir once every 30 minutes during the reaction, and the reaction is carried out for 3 hours. After the reaction is completed, take the precipitate and wash it with deionized water 7 times, and dry the obtained precipitate at 50°C to obtain pretreated silicon powder.

[0080] Step 2: Weigh 5 g of the silicon powder obtained in step 1 and loosely pack it in a ceramic crucible, then place the ceramic crucible in the uniform temperature zone of a tubular furnace; exhaust with high-purity nitrogen at a flow rate of 100 ml / min for 30 minutes, heat to 250°C at a rate of 10°C / min and keep warm for 3 hours, then heat to 800°C at a rate of 10°C / min and keep warm for 2 hours, then cool to room temperature with the furnace and take out the silicon powder.

[0081] Step 3: Soak the silicon powder in acetone for 10 minutes, then rinse it with deionized water for 7 times, and dry it to obtain the silicon powder for use.

[0082] The silicon particles prepared in Examples 1 to 5 of the present invention and Comparative Examples 1 to 4 were used as silicon-based negative electrode materials, and button-type half-cells were assembled for testing, and silicon powder without any treatment was used as a reference.

[0083] The silicon-based negative electrode material, the conductive additive carbon black, and the binder were mixed in a mass ratio of 95:2:3 to form a slurry, which was then coated, dried, cut into pieces, and assembled into negative electrode sheets. A metal lithium sheet was used as the counter electrode, Celgard 2400 was used as the separator, and 1MLiPF6 EC:DMC (1:1Vol%) was used as the electrolyte to assemble a button half-cell. The electrochemical test was carried out on a Land electrochemical instrument at a discharge rate of 0.5C. The results are shown in Table 1.

[0084] Table 1

[0085]

[0086] The expansion rate of the negative electrode plate was tested using an in-situ expansion analyzer. The expansion rate of the plate was detected after 100 cycles of charge and discharge at a 1C discharge rate. The test results are shown in Table 2.

[0087] Table 2

[0088]

[0089] It can be seen from the data in Table 1 and Table 2 that compared with untreated silicon powder, the surface nitrided silicon powder prepared in Examples 1 to 5 of the present invention has better electrochemical performance and lower expansion rate after being prepared into the negative electrode. The reason is that the surface nitridation modification inhibits the pulverization of silicon particles and prevents them from falling off, thereby improving the battery stability and having excellent first coulombic efficiency and first lithium desorption capacity.

[0090] Compared with Example 1, Comparative Example 1 uses an excessively high temperature of 1100° C. for pyrolysis, and the electrochemical performance of the silicon powder obtained as the negative electrode material of a lithium-ion battery is inferior to that of Example 1, and the expansion rate is greater than that of Example 1. The reason is that: the pyrolysis temperature is too high, so that the pyrolysis product is crystallized, and the crystallized product leads to poor electrochemical performance and increased brittleness, so that the first coulomb efficiency and the first lithium removal capacity decrease, and the expansion rate increases;

[0091] Compared with Example 1, Comparative Example 2 uses an overly low temperature of 700°C for pyrolysis, and the electrochemical performance of the silicon powder obtained as the negative electrode material of the lithium ion battery is inferior to that of Example 1, and the expansion rate is greater than that of Example 1. The reason is that: the pyrolysis temperature is too low, the pyrolysis is incomplete, and the effect of nitridation modification is not ideal, which makes the first coulomb efficiency and the first lithium removal capacity decrease, and the expansion rate increases;

[0092] Compared with Example 1, Comparative Example 3 directly performs high-temperature pyrolysis during heat treatment without a preheating process. The electrochemical performance of the silicon powder obtained as a negative electrode material for a lithium-ion battery is inferior to that of Example 1, and the expansion rate is greater than that of Example 1. The reason is that the preheating process is a process in which bond condensation and bond breakage occur between the organic functional groups of polysilazane and low molecular weight substances escape. The lack of this process will lead to incomplete subsequent organic-inorganic conversion, making the effect of nitridation modification unsatisfactory, thereby reducing the first coulomb efficiency and the first lithium removal capacity, and increasing the expansion rate;

[0093] Compared with Example 1, Comparative Example 4 directly heat-treats the silicon powder and deletes the nitrogen source impregnation process. The electrochemical performance of the silicon powder obtained as a negative electrode material for a lithium-ion battery is inferior to that of Example 1, and the expansion rate is greater than that of Example 1. The reason is that: due to the lack of the nitrogen source impregnation process, the subsequent high-temperature treatment cannot achieve the purpose of nitridation modification, thereby reducing the first coulombic efficiency and the first lithium desorption capacity, and increasing the expansion rate.

[0094] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a surface nitrided lithium battery silicon-based negative electrode material, characterized in that: The preparation method comprises the following steps: The silicon powder is immersed in an acid solution for pickling to remove oxygen and impurities, and then repeatedly rinsed with deionized water and dried; The acid-washed silicon powder is immersed in liquid polysilazane, fully stirred and then filtered to obtain silicon powder with the surface impregnated with polysilazane; The silicon powder after the impregnation treatment is heat-treated, and the heat treatment is preheating and then thermal cracking; the preheating temperature is 240°C to 260°C, and the thermal cracking temperature is 800°C to 1000°C; within the preheating temperature range, the polysilazane undergoes a cross-linking reaction, and the bonds between the organic functional groups condense and break; within the thermal cracking temperature range, the organic matter is converted into inorganic matter, and the organic group decomposes to form amorphous silicon nitride; The heat-treated silicon powder is immersed in an organic solvent for cleaning, and then repeatedly rinsed with deionized water. After drying, surface nitrided silicon particles are obtained. The surface of the silicon particles is coated with amorphous silicon nitride and is used as a silicon-based negative electrode material for lithium batteries.

2. The method for preparing a surface nitrided lithium battery silicon-based negative electrode material according to claim 1, characterized in that: The specific operation of the heat treatment is as follows: The silicon powder after the impregnation treatment is loosely packed in a ceramic crucible, and the ceramic crucible is placed in the uniform temperature zone of a tube furnace; nitrogen-containing gas is input to evacuate the inside of the tube furnace; Heat up at a rate of 5℃ / min~10℃ / min, and keep the temperature for 3h±0.5h after the uniform temperature zone reaches the preheating temperature of 240℃~260℃; After the insulation is completed, the temperature is increased at a rate of 5℃ / min~10℃ / min, and the uniform temperature zone is raised to the thermal cracking temperature of 800℃~1000℃ and then maintained for 2h±0.5h; The product is then cooled to room temperature in the furnace to obtain silicon powder with surface nitrided.

3. The method for preparing a surface nitrided lithium battery silicon-based negative electrode material according to claim 2, characterized in that: The nitrogen-containing gas is selected from at least one of nitrogen and ammonia, and its purity is ≥99.999%.

4. The method for preparing a surface nitrided lithium battery silicon-based negative electrode material according to claim 1, characterized in that: The acid solution is a mixed acid solution of 1wt.%~5wt.% hydrofluoric acid and 5wt.%~10wt.% hydrochloric acid.

5. The method for preparing a surface nitrided lithium battery silicon-based negative electrode material according to claim 4, characterized in that: The solid-to-liquid ratio of the silicon powder to the acid solution is 1:10-1:

20.

6. The method for preparing a surface nitrided lithium battery silicon-based negative electrode material according to claim 4, characterized in that: The silicon powder is immersed in the acid solution for pickling for 3h±0.5h.

7. The method for preparing a surface nitrided lithium battery silicon-based negative electrode material according to claim 1, characterized in that: The organic solvent is acetone.

8. A surface nitrided lithium battery silicon-based negative electrode material obtained by the preparation method according to any one of claims 1 to 7.

9. The surface nitrided lithium battery silicon-based negative electrode material according to claim 8, characterized in that: The silicon-based negative electrode material of the lithium battery is silicon particles with amorphous silicon nitride coated on the surface.

Citation Information

Patent Citations

  • Impregnation-curing treatment method of polysilazane, composite material and preparation method of composite material

    CN115724675A

  • Preparation method and application of modified carbon paper negative electrode material

    CN118099422A